Effect of polyvinylpyrrolidone on cerium oxide nanoparticle characteristics prepared by a facile heat treatment technique - Baqer, Anwar Ali; Matori, Khamirul Amin; Al-Hada, Naif Mohammed; Shaari, Abdul Halim; Saion, Elias; Liew, Josephine Ying Chyi (Elsevier, 2017)
An aqueous medium composed of polyvinylpyrrolidone (PVP) and cerium nitrates at calcination temperature was utilised in the production of cerium oxide (CeO2) semiconductor nanoparticles. A variety of analytical approaches was utilized to examine the structural, morphological and optical characteristics of the resulting nanoparticles. Differential thermal (DTA) and thermogravimetric (TGA) analyses, indicated that the best calcination temperatures for achieving CeO2 nanoparticle production were more than 485 °C. The results from Fourier-transform infrared (FTIR) verified the formation of a crystalline structure after calcination procedures were performed to remove residual organic compounds. Additionally, results from X-ray diffraction (XRD) analysis confirmed the cubic fluorite structure of the CeO2 produced. Samples were also analysed by energy dispersive spectroscopy (EDXA) which indicated the existence of O and Ce in the samples. Field emission scanning electron microscopy (FESEM) was used in the characterisation of nanoparticle morphological features. Transmission electron microscopy (TEM) was employed to estimate typical nanoparticle and distribution within sample. This analysis indicated that mean particle sizes were inversely correlated with PVP concentration, with nanoparticle sizes ranging between 12 ± 7 nm at 0.03 g/mL PVP and 6 ± 2 nm at 0.05 g/mL PVP. These results corroborated those obtained by XRD analysis. A UV–vis spectrophotometer was utilised in the demonstration of optical properties and to examine the band gap energy of samples. The potential UV-shielding properties of the nanoparticles were demonstrated by the observed blue shift of the estimated optical energy band, i.e. from 3.35 to 3.43 eV, whilst PL spectra results indicated that decreasing particle size was associated with diminishing photoluminescence intensity.